(untitled) (The Journal of Plant Protection Sciences, 2024)
Plant galls are abnormal growths caused by stimulation of plant cells with the interaction by the nematodes, fungus, bacteria, mites, in sect etc. (2, 24, 26). Galls can be formed in the lamina and petioles of leaves, twigs, buds, flowers or on the roots. Each type of gall producer is specific to a particular kind of plant. The gall is a unique example of a plant pest relationship causing harmful effects such as hypertrophies and tumorous (neoplasmic) outgrowths as well as beneficial effect to the plants in fixing nitrogen by bacteria, actino mycetes and blue-green algae. Damage by the plant galls is not only the aesthetic problem but also cause serious problems to the many host plants including Prosopis cineraria, P. glandulosa var. torreyana and P. velutina (7, 8, 11, 12, 17). In P. cineraria, four distinct types of galls have been reported by various workers (12, 13, 21). Galls damage the stem branches, rachis, leaflets and flowers portions of the Prosopis tree.